ANALISIS KRITIS PENDIDIKAN SAINS DI INDONESIA: (Problematika, Solusi dan Model Keterpaduan Sains Dasar) - Ahmad Khoiri; Nasokah Nasokah; Tesya Amelia; Hefi Slamet (Program Studi Pendidikan Fisika, FITK, UNSIQ, 2020)
Science Indonesia's education has complex problems including didactics, curriculum, content, and facilities that are different from developed science education countries. Research library data collection methods from various review sources to identify problems; solutions or improvement efforts and effective cohesive models recommended in SAINS learning by considering the capabilities and potentials they have. The results of the qualitative descriptive analysis show: 1) Critical Analysis of Indonesian Science education through the standard of teaching materials, learning process, and assessment of laboratory facilities is still not optimal compared to developed science education countries. The point of comparison lies in the orientation of different learning objectives so that the way to teach both models, techniques, assessment, and evaluation is different; 2) Efforts to improve Science learning in Indonesia through SWOT Analysis are the readiness of learning Materials or resources, curriculum policies, professional Teacher HR and adequate facilities through the STEM (Science Technological, Engineering, and Mathematics) approach; 3) The integrated STEM Science integrated model recommended by considering literature studies, the potential and conditions of Indonesia can create a superior generation is facing challenges and global issues and can compete with advanced science education countries without abandoning Pancasila living values as the state ideology